1987
DOI: 10.1159/000226441
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Effect of Didemnin B on Two Tumors of the Rat

Abstract: Didemnin B administered at a dose of 0.06 mg/kg, highest nontoxic dose for the rat, shows a high antitumor activity against Yoshida ascites tumor only after intraperitoneal injection of the drug; supplied by other routes both against T8 sarcoma of Guérin and Yoshida ascites tumor is ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…The compound also exhibited antiviral and antitumor activities more active than didemnin A. Some antitumor tests were also evaluated against human tumor stem cell assay [153] and Yoshida ascites tumor through in vivo analysis [154]. Some antitumor tests were also evaluated against human tumor stem cell assay [153] and Yoshida ascites tumor through in vivo analysis [154].…”
Section: Biological Activitymentioning
confidence: 99%
“…The compound also exhibited antiviral and antitumor activities more active than didemnin A. Some antitumor tests were also evaluated against human tumor stem cell assay [153] and Yoshida ascites tumor through in vivo analysis [154]. Some antitumor tests were also evaluated against human tumor stem cell assay [153] and Yoshida ascites tumor through in vivo analysis [154].…”
Section: Biological Activitymentioning
confidence: 99%
“…Three mice each were randomly assigned to high-and low-dose groups given didemnin B at 1280 mg/kg or 320 mg/kg, or a control group given 0.8 ml of vehicle. Each lowand high-dose mouse was given 272 mg/kg of their total didemnin B dose as [ 3 H]didemnin B. Urine and feces were collected at 3,6,9,12,15,18,21,24,30,36,42,48,60,72,84,96,108,120,132,144,156 and 168 h after administration of [ 3 H]didemnin B. At 168 h, mice were anesthetized with xylazine and ketamine hydrochloride and exsanguinated via cardiac puncture.…”
Section: Animals Dosing and Specimen Collectionmentioning
confidence: 99%
“…Didemnin B (NSC 325319) and related compounds are in preclinical and clinical trials as anticancer, antiviral and immunosuppressive drugs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In mice, didemnin B protected against intraperitoneally (i.p.)…”
Section: Introductionmentioning
confidence: 99%
“…Fimiani 36 reported that doses of 0.06 mg/kg were non-toxic but highly effective against Yoshida ascites tumors in rats. The report also noted, however, that intraperitoneal injection was required, since drug delivery by other routes was ineffective.…”
Section: Antitumor Activitymentioning
confidence: 99%